The impact of parents' years since migration on children's academic achievement - Helena Skyt Nielsen; Beatrice Schindler Rangvid (IZA Journal of Migration, 2012)
In this paper, we employ register data for eight cohorts of second-generation immigrant pupils to identify the impact of each parent's years since migration on their children's school achievements. We exploit variation in years since migration and within-family variation. We find evidence of a positive impact of parents' years since migration on children's academic achievement. Mothers' years of residence tend to be more important for Danish, while fathers' years of residence tend to be more important for math. The effects vary by gender, and family-specific effects influence girls' and boys' educational attainment differently.
Keywords: I21; J12; J620; 330; intergenerational mobility; years since migration; scholastic achievement; immigrant children; second generation; fixed effects